TOXICOLOGICAL SCREENING OF ELLAGIC ACID IN POMEGRANATE FRUIT AND HYDROXYAPATITE COMBINATION AS BONE GRAFT MATERIAL ON BHK-21 FIBROBLAST CELL - Agung Satria Wardhana; Isyana Erlita; Intan Nirwana; Hendrik Setiabudi (FKG Unlam, 2020)
Background: Bone graft is an alternative therapy for periodontitis and other bone destructive lesions. Several studies had revealed Ellagic Acid (EA) ability in increasing osteogenesis process. EA contains polyphenols, such as Ellagitannin, Gallotannin, and Anthocyanin, which demonstrate anti-inflammatory and antibacterial activity as well as growth factor stimulating effect. EA combination with bone graft material (hydroxyapatite) is anticipated to enhance bone osteogenesis yet no investigation was performed to identify its toxicity towards fibroblast cell. Objective: To analyze EA toxicity on fibroblast cell in vitro. Methods: This was a true experimental study using post-test only with control group design. Fibroblast cell was exposed with EA in eight different concentrations: 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4% and 5%. Control group comprised of cell control and media group. All groups were exposed to MTT Assay test and measured using Elisa Reader. Result: The calculation of cell viability value in EA groups at 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4% and 5% concentration were 88.2%, 92.3%, 97.5%, 89.5%, 84.2%, 90.7%, 88.9% and 89.4% respectively. Conclusion: All EA and hydroxyapatite combinations are not toxic towards BHK-21 fibroblast cells.